Transformation of Mathematics Learning Through a Combination of Gamification and Ethnomathematics Approach - Simanjuntak, Sinta Dameria; Fauzi, KMS Muhammad Amin; Mukhtar, Mukhtar; Sitepu, Israil (SAINTIS Publishing, 2024)
This research examines the transformation of mathematics learning through the combination of gamification and the ethnomathematics approach using the literature study method. In an effort to enhance student engagement and understanding, the combination of these two approaches offers significant potential in creating a more engaging and culturally relevant learning experience. Through the analysis of various literature sources, this research explores the concepts, strategies, and best practices that have been implemented in the context of mathematics education. The research findings indicate that gamification can enhance student motivation with game elements, while ethnomathematics enriches learning with local cultural contexts. However, this research also identifies the challenges faced, such as the limited training for educators, resistance to pedagogical changes, and the need for resources that support effective implementation. These findings provide valuable insights for educators, curriculum developers, and researchers in designing innovative and contextual learning approaches, as well as opening up opportunities for further research in the field of mathematics education.